Pengaruh Covid 19 Terhadap Pemenuhan Kebutuhan Primer Dan Peluang Usaha Di Kecamatan Polanharjo - Suhatmi, Erna Chotidjah; Gunaningrat, Rayhan; Karisma, Arya; Rahmawati, Melisa Ari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research to determine the effect of Covid 19 on meeting primary needs and business opportunities. The data were collected using a questionnaire taken from 100 respondents. Based on the results of data quality tests and classical assumption tests, it is followed by a linear regression test to determine the value of t, F and determination. Based on the results of the determination test that the primary fulfillment and business opportunities contributed to the impact of the disaster by 0.828 or 82.80% . while the remaining 7.2% was influenced by other variables outside the model. Testing of each variable is based on the value of t count> t table. The t table value is 0.676, based on the test results it is known that the X1 value of 2.388 means that the impact of the disaster affects the fulfillment of primary needs, with a t table value of 2.388 means the value of t count> table or 2.388> 0.676. Meanwhile, based on the test results it is known that the value of X2 is 11.997, which means that the impact of the disaster has an effect on business opportunities, with a t table value of 11.997, which means the value of t count> table or 11.997> 0.676. Meanwhile, simultaneously the impact of the disaster affects the fulfillment of primary needs and business opportunities. This can be seen based on the calculated F value> F table, the F table value 3.09 while the F count value 233.433.